2019
DOI: 10.7554/elife.43718
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide radicals are emitted by wasp eggs to kill mold fungi

Abstract: Detrimental microbes caused the evolution of a great diversity of antimicrobial defenses in plants and animals. Insects developing underground seem particularly threatened. Here we show that the eggs of a solitary digger wasp, the European beewolf Philanthus triangulum, emit large amounts of gaseous nitric oxide (NO⋅) to protect themselves and their provisions, paralyzed honeybees, against mold fungi. We provide evidence that a NO-synthase (NOS) is involved in the generation of the extraordinary concentrations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 118 publications
0
9
0
1
Order By: Relevance
“…Ground-nesting, immature Hymenoptera (and their food) are vulnerable to attack by soil-borne microbes. Hence, both endogenous and bacterially based defenses are common ( Kaltenpoth et al, 2005 ; Fernández-Marín et al, 2009 ; Strohm et al, 2019 ). For Ptiloglossa , the organic acids (and potentially ethanol) resulting from Apilactobacillus fermentation may suppress microbial invaders ( McFrederick et al, 2018 ; Vuong and McFrederick, 2019 ) analogously to the anti-spoilage properties of lacto-fermented food.…”
Section: Discussionmentioning
confidence: 99%
“…Ground-nesting, immature Hymenoptera (and their food) are vulnerable to attack by soil-borne microbes. Hence, both endogenous and bacterially based defenses are common ( Kaltenpoth et al, 2005 ; Fernández-Marín et al, 2009 ; Strohm et al, 2019 ). For Ptiloglossa , the organic acids (and potentially ethanol) resulting from Apilactobacillus fermentation may suppress microbial invaders ( McFrederick et al, 2018 ; Vuong and McFrederick, 2019 ) analogously to the anti-spoilage properties of lacto-fermented food.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that the female beewolf grows helpful bacteria inside her antennae and transfers some to her young. The bacteria produce antibiotics that protect the larvae and their cocoons from mold [ 19 ]. A similar phenomenon occurs in plants: the genotype of the maternal plant usually controls the color of the seed coat, and the embryonal control of seed coat color is related with phenylalanine and alanine metabolism in the embryo [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, a drastic reduction was observed for mould cells after exposure to the plasma bubbling system could be explained due to the breakage of vesicle and the conidiophores after exposure to cold plasma which leads to cell leakage and loss of viability; in this way, cold plasma damages the fungal cell (Suhem et al 2013). This also may be because indirect plasma contains longer living reactive species like nitric oxide which comes in contact with food materials and kill mould (Surowsky, et al 2015; Strohm et al 2019). The overall finding of our result correlates with Coutinho et al 2018 according to the study, dairy product when exposed to non-thermal plasma treatment, the microbial load in it depends on different factors such as target species of microorganism, the interval of time used for treatment, input power and gas and food composition (Coutinho et al 2018).…”
Section: Microbial Analysismentioning
confidence: 99%